Knockdown of pp32 Increases Histone Acetylation and Ameliorates Cognitive Deficits - Feng, Qiong; Chai, Gao-Shang; Wang, Zhi-Hao; Hu, Yu; Sun, Dong-Sheng; Li, Xiao-Guang; Ma, Rong-Hong; Li, Yi-Rong; Ke, Dan; Wang, Jian-Zhi; Liu, Gong-Ping (Frontiers in Aging Neuroscience, 2017)
Abstract Ageing is a cause of cognitive decline in the elderly and the major risk factor for Alzheimer’s disease, however, aging people are not all destined to develop into cognitive deficits, the molecular mechanisms underlying this difference in cognitive of aging people are obscure. Epigenetic modifications, particularly histone acetylation in the nervous system, play a critical role in regulation of gene expression for learning and memory. An inhibitor of acetyltransferases (INHAT) is reported to suppress histone acetylation via a histone-masking mechanism, and pp32 is a key component of INHAT complex. In the present study, we divided 18 m-old aged mice into the cognitive-normal and the cognitive-impaired group by Morris water maze, and found that pp32 level was significantly increased in the hippocampus of cognitive-impaired aged mice. The mRNA and protein levels of synaptic-associated proteins decreased with reduced dendrite complexity and histone acetylation. Knockdown of pp32 rescued cognitive decline in cognitive-impaired aged mice with restoration of synaptic-associated proteins, the increase of spine density and elevation of histone acetylation. Our study reveals a novel mechanism underlying the aging-associated cognitive disturbance, indicating that suppression of pp32 might represent a promising therapeutic approach for learning and memory impairments.